Symbolism of selected visual art forms in the Bole Traditional Area - Yakubu, Martin Kiipo (2011)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the award of Master of Arts in Art Education.